(untitled) (Revista Logos Ciencia & Tecnología, 2018)
The study presents the behavior of a V concentration system (VCS), as a way to estimate the incident radiation on a flat surface, based on the solar coordinates described in the equations of Spencer, J.W. Increasing the areas of solar capture is a way to expand the solar radiation, captured on a flat surface by reflection. Maximizing the fraction of solar radiation captured; for that purpose, the V-Concentration System (VCS) was developed, adding four flat mirror surfaces to a flat surface, each with an inclination angle to the (flat) pickup surface. A statistical model was described to find a regression and thus expose the specific behavior areas of reflection on the (VCS), with the purpose of finding the optimal angle which achieves an increase in the uptake of radiation on a flat surface.